One Stop On-Site Service Assistance for Business Identification Number (NIB) Management of Micro and Small Business Actors in Sumberagung Mantup Lamongan Village - Kambali, Muhammad; Taufik Prakoso, Ardianas; Yudha Cahya Ningrat, Ahmad; Putri Julia, Nanda (LPPM, STAI Al-Azhar Menganti, 2025)
The assistance activity for the management of Business Identification Numbers (NIB) for Micro and Small Enterprises (MSEs) in Sumberagung Village, Mantup District, Lamongan Regency was carried out as an effort to increase the legality and capacity of village business actors in facing the demands of business formalities in the digital era. Many MSE actors in this village do not have a NIB due to low digital literacy, limited access to information, and the assumption that managing business legality is a complicated and non-urgent process. This activity aims to provide understanding and direct assistance to business actors to be able to manage NIB independently through the Online Single Submission (OSS) system. The methods used in this activity include the observation stage, socialization, technical training, and individual mentoring. Data was obtained through interviews, documentation, and field observations. The results of the assistance show that there has been a significant increase in the number of business actors who have successfully obtained NIB. Before the activity was carried out, only 10% of MSE actors had NIB, while after mentoring it increased to 80%. In addition, there is an increase in public understanding of the importance of business legality and its benefits for business development, such as access to capital and government programs. This activity has an element of novelty in the digital literacy approach based on community assistance, which has proven to be effective in overcoming administrative and technological obstacles among rural business actors. Thus, this activity not only strengthens the legality of micro businesses, but also becomes a model of community empowerment oriented towards economic independence and sustainable village development.